Multiband hysteresis modulation and switching characterization for sliding-mode-controlled cascaded multilevel inverter - Gupta, R.; Ghosh, Arindam; joshi, A. (Institute of Electrical and Electronic Engineers, 2010)
In this paper, a generalized multiband hysteresis modulation and its characterization have been proposed for the sliding-mode control of cascaded H-bridge multilevel-inverter (CHBMLI)-controlled systems. A frequency-domain method is proposed for the determination of net hysteresis bandwidth fora given desired maximum switching frequency of the inverter. The switching transition concept of Tsypkin’s method and the describing function of nonlinear relay have been used for the derivation of results. A hierarchical switching algorithm has been suggested for the modular cells of the cascaded multilevel inverter. The hierarchy of each cell is swapped sequentially to provide the self-balancing capability in case the dc-link voltage is supported by the capacitors. The simulation and experimental verification of the derived results are provided through a single-phase distribution static compensator (DSTATCOM) model. The application in the three-phase system has been shown through simulation studies on a 3.3-kV distribution-system compensation using DSTATCOM. Verification on both single- and three-phase systems is obtained using a five-level cascaded-multilevel-inverter topology.